Using a Combined FE-CA Approach to Investigate Abnormally Large Grains Formed by the Limited Recrystallization Mechanism in a Powder Metallurgy Nickel-Based Superalloy - Yanhui Yang; Boyan Zhang; Xiuquan Chen; Xiaoxuan Wang; Yankai Feng; Lidong Su; Zhengfei Liang; Yifan Liu (Crystals)
Powder nickel-based superalloy is the key material for hot-end components such as turbine disks and gas engine disks in aeroengines, and its microstructure uniformity has an important influence on the disks’ service performance. However, thermomechanical treatments make it easy to produce abnormally large grains (ALGs) in powder superalloy disks. In order to investigate the relationship between the hot deformation conditions and ALGs of powder superalloys, isothermal compression experiments under various deformation conditions were carried out and a FE-CA method was constructed to investigate the ALGs formed by the limited recrystallization mechanism. The results indicate a close relationship between the ALGs formed after the supersolvus treatment of this alloy and the equivalent stress after thermal deformation, and the local dissolution of the γ′ phase in supersolvus heat treatment does not produce ALGs.